The individual and happiness in hyper-consumption society - Pljakic, Goran D.; Pavličević, Slavica M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The individual in the postmodern society increasingly takes an active and productive attitude towards the products of mass culture and gradually builds a critical attitude towards the contents of the mass media, which are often unjustifiably attributed with the absolute power of manipulative effect. However, mass culture, with its tendency towards individualization and the "average", significantly limits the possibilities of an individual to experience the promised happiness in the context of a hyper-consumer society. The tragedy of the hyperconsumer’s happiness lies in his individuality, because in the process of searching for happiness, the individual becomes more and more lonely and alienated. Complete happiness is necessarily connected to other people, which is why it is also fleeting, so that an individual cannot possess it independently.